2012
DOI: 10.1002/pbc.24356
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐arterial chemotherapy is more effective than sequential periocular and intravenous chemotherapy as salvage treatment for relapsed retinoblastoma

Abstract: IAO is significantly superior to sequential periocular-intravenous topotecan-containing regimens in eyes with relapsed intraocular retinoblastoma with a more favorable toxicity profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…Second line treatment options include focal therapies, repeated systemic chemotherapy, 117,118 IAC, 114,119 brachytherapy (internal radiotherapy), 120,121 , EBRT 122124 and whole-eye 121 or proton beam 125 radiation. Criteria for secondary enucleation are not well defined but are dominated by refractory subretinal and vitreous seeding, vitreous haemorrhage and secondary neovascular glaucoma, 117,126 and socio-economic and psychological fatigue to save an eye with poor vision.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Second line treatment options include focal therapies, repeated systemic chemotherapy, 117,118 IAC, 114,119 brachytherapy (internal radiotherapy), 120,121 , EBRT 122124 and whole-eye 121 or proton beam 125 radiation. Criteria for secondary enucleation are not well defined but are dominated by refractory subretinal and vitreous seeding, vitreous haemorrhage and secondary neovascular glaucoma, 117,126 and socio-economic and psychological fatigue to save an eye with poor vision.…”
Section: Managementmentioning
confidence: 99%
“…133135 The efficacy of intravitreal and IAC chemotherapy may ultimately eliminate the need for EBRT, even as second line therapy. 136 A combination of repeat IAC and intravitreal chemotherapy may play an important part in saving eyes that have failed IVC, radiation or IAC 119,130,131 However, in general, extensive treatments over a long time to save an eye may increase family stress, decrease family resources, 108 and risk metastases and death. 114,116,129 …”
Section: Managementmentioning
confidence: 99%
“…Even among them, to our knowledge, only two groups outside Japan have reported more than 20 patients (Gobin et al 2011;Venturi et al 2013). Case reports or shorter series, comparable to our experience, were reported by other groups (Vajzovic et al 2010;Shields et al 2011b;Valero Garcia et al 2013;Materin et al 2013;Muen et al 2012;Schaiquevich et al 2013). Because the safety and efficacy of this treatment outside the major referral centres was unknown, we decided to implement a strategy under a formal phase II national-wide study to obtain rigorous data.…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al [47] [49] showed excellent control of macular retinoblastoma. Thampi et al [50] noted 86% response rate in groups A, B, and C but only 38% response in groups D and E. In a small cohort of 18 eyes, Schaiquevich et al [51] found that IAC was more effective than POC or IVC for treatment of relapsed retinoblastoma. A two-drug IAC regimen was explored by Francis et al [52], and a three-drug regiment by Marr et al [53].…”
Section: When To Use Intra-arterial Chemotherapymentioning
confidence: 97%